Determination of Effective Moisture Diffusivity Considering Shrinkage for Vibration-Assisted Infrared Drying of Pumpkin - Jongyingcharoen Jiraporn Sripinyowanich; Naweera Worawit; Sangruangnak Sakawrat; Assawadejmethakul Achira (BIO Web of Conferences, 2025)
Drying characteristics and physical properties of pumpkin slices during vibration-assisted infrared (VIR), infrared (IR), and hot air (HA) drying were investigated. VIR drying exhibited the highest drying rate (0.1 g water/g dry matter·min) and shortest drying time (100 min), with drying efficiency influenced by IR intensity. Pumpkin slices dried under VIR drying at a middle IR intensity of 750 W/m² demonstrated superior product properties. Shrinkage was linearly correlated with moisture ratio. Effective moisture diffusivity (Deff) ranged from 1.44×10-8 to 5.78×10-8 m2/s for HA and VIR drying, respectively. Incorporating shrinkage effects, Deff-S decreased linearly with decreasing moisture ratio. Deff-S exhibited a strong negative correlation with shrinkage and a strong positive correlation with moisture content, moisture ratio, projected area, and volume.